About a Play: Stanley Middleton's Pentrich Revolution. (10th September 2022) - Steedman, Carolyn
Abstract: A school play about the Pentrich Revolution (1817) and Jeremiah Brandreth its 'leader', scripted in 1970–71 by teacher and novelist Stanley Middleton, reveals the history of teaching about Pentrich, to adults and children, over the previous century. Middleton's use of the Nottinghamshire dialect to write history, in the play and his many novels, is a focus of the article.